Objetos indígenas para o mercado: produção, intercâmbio, comércio e suas transformações. Experiências Ka’apor e Mebêngôkre-Kayapó - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2015)
For many indigenous peoples of the Amazon, the commercialization of material culture provides an important opportunity to generate income. Expert artisans and many families of the villages devote their time to produce cultural objects, specifically for this purpose. Several practices and meanings are involved in the production and exchange (monetary or otherwise) of these objects. At the same time, there are constant demands from the market at the regional and national level, and it is still very difficult to create a niche for indigenous craft production. Considering the ethnographic contexts of the Ka’apor and Mebêngôkre Kayapó indigenous peoples (Alto Turiaçu Indigenous Reserve – Maranhão and Las Casas and Kayapó Indigenous Reserves – Pará, respectively),- we discuss the processes of production, exchange and commercialization of indigenous objects and the relation to market practice and logic, while also examining indigenous interpretations and positions with respect to these issues. Moreover, we examine the possible legal implications engaged in the re-valorization and protection of indigenous knowledge and heritage, as well as the environment that provides the raw materials for cultural objects. In these terms, we also consider the impact on indigenous initiatives upon entering the market.
Indigenous objects for the market: production, exchange, trade and its transformations. Ka’apor and Mebêngôkre-Kayapó experiences
Keywords: Objetos Indígenas; Produção; Comercialização; Mercado; Ka’apor; Mebêngôkre-Kayapó.; CNPQ::CIENCIAS HUMANAS